Prevalence of Human T-lymphotropic virus type 1 and 2 among blood donors in Manaus, Amazonas State, Brazil - Morais, Márcia Poinho EncarnaçÃo de (2017)
Introduction: Human T-lymphotropic virus type 1 and 2 (HTLV-1/2) is endemic in Brazil, but few studies have investigated the seroprevalence of HTLV and its subtypes among blood donors in the capital city Manaus, Amazonas State, Brazil. Aim: To estimate the seroprevalence of HTLV-1/2 and to identify circulating subtypes among blood donors in Manaus. Materials and Methods: Blood donors (2001-2003) were screened for HTLV-1/2 antibodies by ELISA. Positive results were confirmed and subtyped by Western blot assays. Prevalence rates were calculated and compared with demographic data. Results: Among the 87,402 individuals screened, 116 (0.13%) were seropositive for HTLV-1/2. A second sample (76/116) was collected and retested by HTLV-1/2 ELISA, of which only 41/76 were positive. Western blot confirmed HTLV infection in 24/41 retested blood donors [HTLV-1 (n=16), HTLV-2 (n=5) and HTLV-untypable (n=3)]. Discussion: HTLV-1 and HTLV-2 are prevalent among blood donors in Manaus. However, additional studies are needed to comprehend the epidemiology of HTLV-1/2 in Amazonas not only to understand the pathophysiology of the disease providing adequate medical assistance, but also to reduce or block virus transmission.